A trajetória das alterações semânticas nas línguas e os seus reflexos no campo do ensino de língua estrangeira e da tradução - Sabino, Marilei Amadeu [UNESP] (My University, 2011)
The purpose of this study is to reflect on some formally similar lexical units belonging to different foreign languages that although having had the same origin, their meanings today are considerably different from their original meanings. This complex process is understood, however, when a diachronic path of these lexical units is established in order to find justification or probable occurrences for the causes that triggered the semantic changes observed. These reflections aim to foster discussion about the consequences of such changes in the emergence of the so-called “false cognates”.

O objetivo deste estudo é refletir sobre algumas lexias formalmente semelhantes, pertencentes a diferentes línguas estrangeiras que, embora tenham tido a mesma origem, apresentam, hoje, sentidos que se desviaram consideravelmente dos seus significados originais. Esse complexo processo é compreendido, entretanto, quando se estabelece um percurso diacrônico das lexias de interesse, de modo a encontrar justificativas ou ocorrências prováveis para as causas que desencadearam as alterações semânticas observadas. Estas reflexões pretendem fomentar discussões sobre os reflexos de tais alterações no surgimento dos chamados “falsos cognatos”.
Keywords: mudanças semânticas; línguas românicas; ensino de línguas; tradução; falsos cognatos; semantic changes; romance languages; language teaching; translation; false cognates